Answer:
6
Step-by-step explanation:
m = 3
n = 1
Equation
m(m - n) Substitute the givens
Solution
3(3 -1 ) Evaluate what is inside the brackets.
3(2) multiply
6
Answer:
m=3 and n-1 ,find m2- mn
Step-by-step explanation:
A bank features a savings account that has an annual percentage rate of r=5.2% with interest compounded quarterly. Marcus deposits $8,500 into the account.
The account balance can be modeled by the exponential formula S(t)=P(1+rn)^nt, where S is the future value, P is the present value, r is the annual percentage rate written as a decimal, n is the number of times each year that the interest is compounded, and t is the time in years.
(A) What values should be used for P, r, and n?
P= _____ , r=______ , n=________
(B) How much money will Marcus have in the account in 7 years?
Answer = $______ .
Round answer to the nearest penny.
Answer:
Part A)
[tex]P=\$8,500\\ r=0.052\\n=4[/tex]
Part B) [tex]S(7)=\$12,203.47[/tex]
Step-by-step explanation:
we know that
The compound interest formula is equal to
[tex]S(t)=P(1+\frac{r}{n})^{nt}[/tex]
where
S is the Future Value
P is the Present Value
r is the rate of interest in decimal
t is Number of Time Periods
n is the number of times interest is compounded per year
Part A)
in this problem we have
[tex]P=\$8,500\\ r=5.2\%=5.2/100=0.052\\n=4[/tex]
Part B) How much money will Marcus have in the account in 7 years?
we have
[tex]t=7\ years\\ P=\$8,500\\ r=0.052\\n=4[/tex]
substitute in the formula above
[tex]S(7)=8,500(1+\frac{0.052}{4})^{4*7}[/tex]
[tex]S(7)=8,500(1.013)^{28}[/tex]
[tex]S(7)=\$12,203.47[/tex]
In this problem, we find that Marcus should use the values P = $8,500, r = 0.052 and n = 4 for the given savings account. After calculating, we conclude that Marcus would have approximately $11,713.69 in the account after 7 years.
Explanation:This problem involves the concept of compound interest in mathematics. Let's break it down:
For part (A), we are given that the initial deposit or the present value P is $8,500, the annual percentage rate, r, is 5.2% (but for the formula we need to use this as a decimal, so divide by 100: r = 0.052), and the interest is compounded quarterly, or 4 times a year so n = 4.For part (B), we need to find out the future value S of the deposit after 7 years.We use the formula S(t)=P(1+rn)^(nt):
S(7) = 8500(1 + 0.052/4)^(4*7)
By calculating the above, we find the balance after seven years to be approximately $11,713.69 when rounded to the nearest penny.
Learn more about Compound Interest here:https://brainly.com/question/14295570
#SPJ3
The average car sold from Dealership A is $25,700. If the sales person receives 1.5% commission on the price of the car, how much commission is made on average per car sold?
Answer:
385.5 USD
Step-by-step explanation:
If an average car is sold for 25,700 USD, and the sales person gets 1.5% commission of it, we can easily get to the amount of money that the sales person managed to get from each sale.
The 25,700 should be divided by 100, as that is number of total percentage:
25,700 / 100 = 257
So we have 1% being 257 USD, but we need 1.5%, so we should multiple the 257 USD by 1.5%:
257 x 1.5 = 385.5
So we get a result of 385.5 USD, which is the amount the sales person makes from commissions on average per sold car.
true or false
x=3 when 5*6\x=10
1. If x[tex]y^{2}[/tex] and xy are perfect squares, where x and y are positive integers, what is the smallest value of x + y?
Answer:
8
Step-by-step explanation:
xy^2 = k*k y^2 x = k * k so x has to be a perfect square.
xy is a perfect square which means that since x is a perfect square (see above) then y will have to be as well
There is nothing that prohibits x = 4 and y = 4 as being the answer where x = y.
I think the smallest possible value for x + y is 8.
This excludes any possibility of 1 or 0 in some combination, although I would look into 1.
Which of the following reveals the minimum value for the equation 2x2 − 4x − 2 = 0?
2(x − 1)2 = 4
2(x − 1)2 = −4
2(x − 2)2 = 4
2(x − 2)2 = −4
Answer:
[tex]2(x-1)^{2}=4[/tex]
Step-by-step explanation:
we have
[tex]2x^{2} -4x-2=0[/tex]
This is the equation of a vertical parabola open upward
The vertex is a minimum
Convert the equation into vertex form
Group terms that contain the same variable and move the constant to the other side
[tex]2x^{2} -4x=2[/tex]
Factor the leading coefficient
[tex]2(x^{2} -2x)=2[/tex]
[tex]2(x^{2} -2x+1)=2+2[/tex]
[tex]2(x^{2} -2x+1)=4[/tex]
Rewrite as perfect squares
[tex]2(x-1)^{2}=4[/tex] -----> this is the answer
The vertex is the point (1,-4)
Determine whether the relation represents y as a function of x.
Which graph shows the solution to the inequality |x+3| >2
Answer:
The answer is B, given the module of a number has always a positive value
Answer:
Answer is B.
SECOND NUMBER LINE
Step-by-step explanation:
what’s the inverse function
Answer:
[tex]f^{-1}(x)=-2x+6[/tex].
Step-by-step explanation:
[tex]y=f(x)[/tex]
[tex]y=3-\frac{1}{2}x[/tex]
The biggest thing about finding the inverse is swapping x and y. The inverse comes from switching all the points on the graph of the original. So a point (x,y) on the original becomes (y,x) on the original's inverse.
Sway x and y in:
[tex]y=3-\frac{1}{2}x[/tex]
[tex]x=3-\frac{1}{2}y[/tex]
Now we want to remake y the subject (that is solve for y):
Subtract 3 on both sides:
[tex]x-3=-\frac{1}{2}y[/tex]
Multiply both sides by -2:
[tex]-2(x-3)=y[/tex]
We could leave as this or we could distribute:
[tex]-2x+6=y[/tex]
The inverse equations is [tex]y=-2x+6[/tex].
Now some people rename this [tex]f^{-1}[/tex] or just call it another name like [tex]g[/tex].
[tex]f^{-1}(x)=-2x+6[/tex].
Let's verify this is the inverse.
If they are inverses then you will have that:
[tex]f(f^{-1}(x))=x \text{ and } f^{-1}(f(x))=x[/tex]
Let's try the first:
[tex]f(f^{-1}(x))[/tex]
[tex]f(-2x+6)[/tex] (Replace inverse f with -2x+6 since we had [tex]f^{-1})(x)=-2x+6[/tex]
[tex]3-\frac{1}{2}(-2x+6)[/tex] (Replace old output, x, in f with new input, -2x+6)
[tex]3+x-3[/tex] (I distributed)
[tex]x[/tex]
Bingo!
Let's try the other way.
[tex]f^{-1}(f(x))[/tex]
[tex]f^{-1}(3-\frac{1}{2}x)[/tex] (Replace f(x) with 3-(1/2)x since [tex]f(x)=3-\frac{1}{2}x[/tex])
[tex]-2(3-\frac{1}{2}x)+6[/tex] (Replace old input, x, in -2x+6 with 3-(1/2)x since [tex]f(x)=3-\frac{1}{2}x[/tex])
[tex]-6+x+6[/tex] (I distributed)
[tex]x[/tex]
So both ways we got x.
We have confirmed what we found is the inverse of the original function.
Answer:
[tex]\laege\boxed{f^{-1}(x)=-2x+6}[/tex]
Step-by-step explanation:
[tex]f(x)=3-\dfrac{1}{2}x\to y=3-\dfrac{1}{2}x\\\\\text{Exchange x to y and vice versa:}\\\\x=3-\dfrac{1}{2}y\\\\\text{Solve for}\ y:\\\\3-\dfrac{1}{2}y=x\qquad\text{subtract 3 from both sides}\\\\-\dfrac{1}{2}y=x-3\qquad\text{multiply both sides by (-2)}\\\\\left(-2\!\!\!\!\diagup^1\right)\cdot\left(-\dfrac{1}{2\!\!\!\!\diagup_1}y\right)=-2x-3(-2)\\\\y=-2x+6[/tex]
In ΔBCA, CA = 15 cm, CF = 7 cm, BH = 3 cm. Find the perimeter of ΔBCA.
25 cm
35 cm
36 cm
46 cm
Answer:
The perimeter of the triangle is equal to 36 cm
Step-by-step explanation:
we know that
The inscribed circle contained in the triangle BCA is tangent to the three sides
we have that
BF=BH
CF=CG
AH=AG
step 1
Find CG
we know that
CF=CG
so
CF=7 cm
therefore
CG=7 cm
step 2
Find AG
we know that
CA=AG+CG
we have
CA=15 cm
CG=7 cm
substitute
15=AG+7
AG=15-7=8 cm
step 3
Find AH
Remember that
AG=AH
we have
AG=8 cm
therefore
AH=8 cm
step 4
Find BF
Remember that
BF=BH
BH=3 cm
therefore
BF=3 cm
step 5
Find the perimeter of the triangle
P=AH+BH+BF+CF+CG+AG
substitute the values
P=8+3+3+7+7+8=36 cm
The perimeter of ΔBCA (triangle BCA) is 36 cm
Perimeter of a triangle
The perimeter of a triangle is the sum of the length of the three sides.
The inscribed circle contained in the triangle BCA is tangent to the three sides
Therefore,
BF = BH = 3 cm
CF = CG = 7 cm
AH = AG = 15 - 7 = 8 cm
Therefore,
perimeter = CA + BC + BA
perimeter = 15 + 3 + 7 + 3 + 8
Therefore,
perimeter = 15 + 10 + 11
perimeter = 15 + 21
perimeter = 36 cm
learn more on perimeter here: https://brainly.com/question/15450681
Write the slope-intercept form of the equation that passes through the point (2, 3) and is perpendicular to the line y = 5/8x - 4
Answer:
[tex]\large\boxed{y=-\dfrac{8}{5}x+\dfrac{31}{5}}[/tex]
Step-by-step explanation:
[tex]\text{The slope-intercept form of an equation of a line:}\\\\y=mx+b\\\\m-slope\\b-y-intercept[/tex]
[tex]\text{Let}\\\\k:y=m_1x+b_1\\\\l:y=m_2x+b_2\\\\l\ \perp\ k\iff m_1m_2=-1\to m_2=-\dfrac{1}{m_1}\\\\l\ \parallel\ k\iff m_1=m_2\\\\--------------------------[/tex]
[tex]\text{We have:}\\\\y=\dfrac{5}{8}x-4\to m_1=\dfrac{5}{8}\\\\\text{The slope of a perpendicular line:}\ m_2=-\dfrac{1}{\frac{5}{8}}=-\dfrac{8}{5}\\\\\text{The equation:}\\\\y=-\dfrac{8}{5}x+b\\\\\text{Put the coordinates of the point (2, 3) to the equation:}\\\\3=-\dfrac{8}{5}(2)+b\qquad\text{solve for}\ b\\\\3=-\dfrac{16}{5}+b\qquad\text{add}\ \dfrac{16}{5}\ \text{to both sides}\\\\\dfrac{15}{5}+\dfrac{16}{5}=b\to b=\dfrac{31}{3}\\\\\text{Finally:}\\\\y=-\dfrac{8}{5}x+\dfrac{31}{5}[/tex]
Multiply (9-4i)(2+5i)
(9 - 4i)(2 + 5i)
To solve this question you must FOIL (First, Outside, Inside, Last) like so
First:
(9 - 4i)(2 + 5i)
9 * 2
18
Outside:
(9 - 4i)(2 + 5i)
9 * 5i
45i
Inside:
(9 - 4i)(2 + 5i)
-4i * 2
-8i
Last:
(9 - 4i)(2 + 5i)
-4i * 5i
-20i²
Now combine all the products of the FOIL together like so...
18 + 45i - 8i - 20i²
***Note that i² = -1; In this case that means -20i² = 20
18 + 45i - 8i + 20
Combine like terms:
38 - 37i
^^^This is your answer
Hope this helped!
~Just a girl in love with Shawn Mendes
Global online music sales have exploded. It was expected that music lovers would spend 2 billion for online music in 2007, in scientific notation this number is?
Pls help ive been struggling on this for a while
Answer:
[tex]2*10^{9}[/tex]
Step-by-step explanation:
we know that
One billion is equal to one thousand million
1 billion is equal to 1,000,000,000
so
Multiply by 2
2 billion is equal to 2,000,000,000
Remember that
In scientific notation, a number is rewritten as a simple decimal multiplied by 10 raised to some power, n
n is simply the number of zeroes in the full written-out form of the number
In this problem n=9
so
[tex]2,000,000,000=2*10^{9}[/tex]
The length of a rectangle frame is represented by the expression 2x +8, and the width of the rectangle frame is represented by the expression 2x +6 what is the width of the rectangle frame that has a total area of 160 Square inches
Final answer:
The width of the rectangle frame with a total area of 160 square inches, and expressions for length (2x + 8) and width (2x + 6), is found to be 10 inches.
Explanation:
To solve for the width of the rectangle frame with an area of 160 square inches, where the length is represented by 2x + 8 and the width by 2x + 6, we need to set up an equation using the formula for the area of a rectangle, which is length × width. With the given area of 160 square inches, the equation is:
(2x + 8)(2x + 6) = 160
Let's expand this and solve for x:
4x² + 12x + 16x + 48 = 160
4x² + 28x + 48 = 160
4x² + 28x - 112 = 0
Divide everything by 4 to simplify:
x²+ 7x - 28 = 0
Factor this quadratic equation:
(x + 14)(x - 2) = 0
x = -14 or x = 2
Since a width cannot be negative, x = 2
Now, to find the width, replace x in the width expression:
Width = 2x + 6
Width = 2(2) + 6 = 4 + 6 = 10 inches
Thus, the width of the rectangle frame is 10 inches.
Classify the following triangle. Check all that apply.
Answer:
obtuse, isosceles
Step-by-step explanation:
We have two angles that have the same measure - that means two sides are equal length. That means the triangle is isosceles
We have one angle that is greater than 90 degrees - that tells us the triangle is obtuse
Which expression is equivalent to ((2a^-3 b^4)^2/(3a^5 b) ^-2)^-1
Answer:
[tex]\large\boxed{\dfrac{1}{36a^4b^{10}}}[/tex]
Step-by-step explanation:
[tex]\left(\dfrac{\left(2a^{-3}b^4\right)^2}{\left(3a^5b\right)^{-2}}\right)^{-1}\qquad\text{use}\ a^{-1}=\dfrac{1}{a}\\\\=\dfrac{\left(3a^5b\right)^{-2}}{\left(2a^{-3}b^4\right)^2}\qquad\text{use}\ (ab)^n=a^nb^n\\\\=\dfrac{3^{-2}(a^5)^{-2}b^{-2}}{2^2(a^{-3})^2(b^4)^2}\qquad\text{use}\ (a^n)^m=a^{nm}\\\\=\dfrac{3^{-2}a^{(5)(-2)}b^{-2}}{4a^{(-3)(2)}b^{(4)(2)}}=\dfrac{3^{-2}a^{-10}b^{-2}}{4a^{-6}b^8}\qquad\text{use}\ \dfrac{a^n}{a^m}=a^{n-m}[/tex]
[tex]=\dfrac{3^{-2}}{4}a^{-10-(-6)}b^{-2-8}=\dfrac{3^{-2}}{4}a^{-4}b^{-10}\qquad\text{use}\ a^{-n}=\dfrac{1}{a^n}\\\\=\dfrac{1}{3^2}\cdot\dfrac{1}{4}\cdot\dfrac{1}{a^4}\cdot\dfrac{1}{b^{10}}=\dfrac{1}{36a^4b^{10}}[/tex]
Answer:
1 / 36a^4 b^10
Step-by-step explanation:
Which one of the following is equal to 1hector area? 10000m/square 10000m/square 100m/square
100000m/square
Answer:
10,000 m/square
Step-by-step explanation:
we know that
A hectare is a unit of area equal to [tex]10,000\ m^{2}[/tex]
The symbol is Ha
Verify each case
case 1) 10,000 m/square
The option is true
case 2) 100 m/square
The option is false
case 3) 100,000 m/square
The option is false
which value is equivalent to (7x5x2/7x3)^2 x (5^0/2^-3)^3 x2^-9?
Answer:
100/9
Step-by-step explanation:
(7*5*2/7*3)² * (5^0/2^-3)³ * 2^-9
Solution:
We know that any number with power 0 = 1
(7*5*2/7*3)² * (1/2^-3)³ * 2^-9
Now cancel out 2 by 2
= (7*5*2/7*3)² * (1/1^-3)³ * 1^-9
=(70/21)² * (1)³/(1^-3)³ * 1^-9
=(10/3)^2 * 1/1^-1 * 1/1^9
=100/9 *1 *1
=100/9....
Which terms could be used as the first term of the expression below to create a polynomial written in standard form? Check all that apply.
+ 8r2s4 – 3r3s3
s5
3r4s5
–r4s6
–6rs5
Answer:
[tex]3r^{4}s^{5}\\-r^{4}s^{6}[/tex]
Step-by-step explanation:
The standard form of a polynomial is when its term of highest degree is at first place.
In this case, we have two variables. The grade of each term is formed by the sum of its exponents. That means both given terms have a degree of six. So, the right answers must have a higher degree.
Therefore, the right answers are the second and third choice, because their degrees are 9 and 10 respectively.
120 is increased by d % and increased by 25% . What is the result ?
Please see attached image for complete answer and steps in detail.
Answer:
The result is 150 + 1.5d
Step-by-step explanation:
We want to translate the wordings into algebraic expression.
Firstly, we increase 120 by d%
d% = d/100
So increasing 120 by d % means;
120 + (d/100 * 120)
= 120 + 1.2d
Then increase this by 25%
= (120 + 1.2d) + 25/100(120 + 1.2d)
= 120 + 1.2d + (120+1.2d)/4
= 120 + 1.2d + 30 + 0.3d
= 120 + 30 + 1.2d + 0.3d
= 150 + 1.5d
a^-3 over a^-2b^-5 write without rational notation and move all terms to numerator
Answer:
[tex]\large\boxed{\dfrac{a^{-3}}{a^{-2}b^{-5}}=a^{-1}b^5}[/tex]
Step-by-step explanation:
[tex]\dfrac{a^{-3}}{a^{-2}b^{-5}}=a^{-3}\cdot\dfrac{1}{a^{-2}}\cdot\dfrac{1}{b^{-5}}\qquad\text{use}\ x^{-n}=\dfrac{1}{x^n}\\\\=a^{-3}\cdot a^2\cdot b^5\qquad\text{use}\ x^n\cdot x^m=x^{n+m}\\\\=a^{-3+2}b^5=a^{-1}b^5[/tex]
Find the equation of the axis of symmetry and the coordinates of the vertex of the graph of the function y = 2x2 + 4x –3.
Answer:
Equation of the parabola: [tex]y = 2x^{2} + 4x - 3[/tex].
Axis of symmetry: [tex]x= -1[/tex].
Coordinates of the vertex: [tex]\displaystyle \left(-1, -5\right)[/tex].
Step-by-step explanation:
The axis of symmetry and the coordinates of the vertex of a parabola can be read directly from its equation in vertex form.
[tex]y = a(x-h)^{2} +k[/tex].
The vertex of this parabola will be at [tex](h, k)[/tex]. The axis of symmetry will be [tex]x = h[/tex].
The equation in this question is in standard form. It will take some extra steps to find the vertex form of this equation before its vertex and axis of symmetry can be found. To find the vertex form, find its coefficients [tex]a[/tex], [tex]h[/tex], and[tex]k[/tex].
Expand the square in the vertex form using the binomial theorem.
[tex]y = a(x-h)^{2} +k[/tex].
[tex]y = a(x^{2} - 2hx + h^{2}) +k[/tex].
By the distributive property of multiplication,
[tex]y = (ax^{2} - 2ahx + ah^{2}) +k[/tex].
Collect the constant terms:
[tex]y = ax^{2} - 2ahx + (ah^{2} +k)[/tex].
The coefficients in front of powers of [tex]x[/tex] shall be the same in the two forms. For example, the coefficient of [tex]x^{2}[/tex] in the given equation is [tex]2[/tex]. The coefficient of [tex]x^{2}[/tex] in the equation [tex]y = ax^{2} - 2ahx + (ah^{2} +k)[/tex] is [tex]a[/tex]. The two coefficients need to be equal for the two equations to be equivalent. As a result, [tex]a = 2[/tex].
Similarly, for the term [tex]x[/tex]:
[tex]-2ah = 4[/tex].
[tex]\displaystyle h = -\frac{2}{a} = -1[/tex].
So is the case for the constant term:
[tex]ah^{2} + k = -3[/tex].
[tex]k = -3 - ah^{2} = -5[/tex].
The vertex form of this parabola will thus be:
[tex]y = 2(x -(-1))^{2} + (-5)[/tex].
The vertex of this parabola is at [tex](-1, -5)[/tex].
The axis of symmetry of a parabola is a vertical line that goes through its vertex. For this parabola, the axis of symmetry is the line [tex]x = -1[/tex].
A box contains 90 coins, only dimes and nickels. The amount of money in the box is $6.00. How many dimes and how many nickels are in the box?
The number of dimes is
The number of nickels is
Answer:
60 nickles and 30 dimes
Step-by-step explanation:
60 $0.05=3.00
30 $.10=3.00
60+30=90
In the box, there are 30 dimes and 60 nickels, as determined by solving a system of equations based on the total number of coins and their value.
Explanation:The box contains both dimes and nickels, totaling an amount of money of $6.00. Because a dime is worth $0.10 and a nickel is worth $0.05, we can set up a system of equations to solve this problem.
Let's denote the number of dimes as x and the number of nickels as y. Thus, our equations are x + y = 90 (since the total number of coins is 90) and 0.10x + 0.05y = 6 (since the total value of the coins is $6.00).
Solving these equations will give us the number of dimes and nickels in the box. Doubling the second equation gives us 0.20x + 0.10y = 12. We can subtract the first equation from this to solve for x, giving us x = 30. Substituting x=30 into the first equation, y = 90 - 30, so y = 60. So, there are 30 dimes and 60 nickels in the box.
Learn more about Systems of Equations here:https://brainly.com/question/35467992
#SPJ2
Which is the graph of the equation y = -3x- 1
Neither of those two graphs do the trick, but if I saw the rest of the answer choices, then I would be happy to assist you.
simplify (2x^4y^3) x (6x^3y^2)
Answer:
[tex]\large\boxed{(2x^4y^3)(6x^3y^2)=6x^7y^5}[/tex]
Step-by-step explanation:
[tex](2x^4y^3)(6x^3y^2)\\\\=(2)(3)(x^4x^3)(y^3y^2)\qquad\text{use}\ a^na^m=a^{n+m}\\\\=6x^{4+3}y^{3+2}\\\\=6x^7y^5[/tex]
Audrey has x pounds of red grapes and y pounds of
green grapes. She has less than 5 pounds of grapesin
all.
Which are reasonable solutions for this situation?
Check all that apply.
D(-1,2)
(1.3.5)
D (2, 2)
(4.5, 0.5)
(5,0)
Answer:
(2,2)
Step-by-step explanation:
10 points for this! btw it’s really easy to some people so yea
Answer:
C
step-by-step explanation:
you just have to subtract them 9/16-1/4=8/12
Sheila is looking at some information for the obstacle course she is interested in completing. The x-coordinate is the number of the obstacle, while the y-coordinate is the average time to complete the obstacle, measured in minutes.
(1, 8.25), (2, 9.075), (3, 9.9825), (4, 10.98075)
Help Sheila use an explicit formula to find the average time she will need for the 8th obstacle.
f(8) = 8.25(1.1)^8; f(8) = 17.685
f(8) = 8.25(1.1)^7; f(8) = 16.077
f(8) = 1.1(8.25)^7; f(8) = 2861345
f(8) = 1.1(8.25)^8; f(8) = 23606102
Answer:
f(8) = 8.25(1.1)^7; f(8) = 16.077
Step-by-step explanation:
In order to calculate the explicit formula we need to look at the y coordinates. All the options list the formula of a Geometric Sequence, so we will find which sequence defines the given coordinates:
The sequence is:
8.25, 9.075, 9.9825, 10.98075
f(1) = First term of the Sequence = 8.25
r = Common Ratio = Ratio of two consecutive terms = [tex]\frac{9.075}{8.25}[/tex] = 1.1
The explicit formula for a geometric sequence is:
[tex]f(n)=f(1)(r)^{n-1}[/tex]
Using the values, we get:
[tex]f(n)=8.25(1.1)^{n-1}[/tex]
For 8th term, we have to replace n by 8:
[tex]f(8)=8.25(1.1)^{8-1}\\\\ f(8)=8.25(1.1)^{7} \\\\ f(8)=16.077[/tex]
So, second option gives the correct answer: f(8) = 8.25(1.1)^7; f(8) = 16.077
Answer:
B // f(8) = 8.25(1.1)^7; f(8) = 16.077
Step-by-step explanation:
I'm Pretty Sure She's Got It ^^^
John was 40 years old in 1995 while his father was 65.In what year was John exactly half his father's age?
Answer:
1980.
Step-by-step explanation:
John was born in 1995 - 40 = 1955.
His father was born in 1995 - 65 = 1930.
Let x be Johns age and his father 2x
1955 + x = 1930 + 2x
1955 - 1930 = 2x - x
x = 25
So the year is 1955 + 25 = 1980..
In that year John was 25 and his father was 50.
Select the correct answer from each drop-down menu.
A rope is cut into three pieces. The lengths are given as 2ab(a − b), 3a2(a + 2b), and b2(2a − b).
The expression representing the total length of the rope is .
If a = 2 inches and b = 3 inches, the total length of the rope is inches.
math
Answer:
1) [tex]3 a^3 + 8 a^2 b - b^3[/tex]
2) 93 inches
Step-by-step explanation:
1) We know that the lenghts are given by these expressions:
[tex]2ab(a - b)\\\\3a^2(a + 2b)\\\\b^2(2a - b)[/tex]
Then, we need to add them in order to find the expression that represents the total length of the rope:
- Apply Distributive property.
- Add the like terms.
Then:
[tex]=2ba^2-2ab^2+3a^3+6ba^2+2ab^2-b^3\\\\=3 a^3 + 8 a^2 b - b^3[/tex]
2) Knowing that:
[tex]a=2in\\\\b=3in[/tex]
We must substitute these values into [tex]3 a^3 + 8 a^2 b - b^3[/tex] in order to caculate the total lenght of the rope. This is:
[tex]3 (2in)^3 + 8 (2in)^2 (3in) - (3in)^3=93in[/tex]
Find the value of y.
Answer:
=6√3 the third option.
Step-by-step explanation:
We can use the Pythagoras theorem to find the value of y. We need two equations that include y.
a²+b²=c²
c=9+3=12
x²+y²=12²
x²=144 - y².........i (This is the first equation)
We can also express it in another way but let us find the perpendicular dropped to c.
perpendicular²= x²-3²=x²-9 according to the Pythagoras theorem.
y²=(x²-9)+9²
y²=x²+72
x²=y²-72....ii( this is the second equation
Let us equate the two.
y²-72=144-y²
2y²=144+72
2y²=216
y²=108
y=√108
In Surd form √108=√(36×3)=6√3
y=6√3